The effects of mindfulness-based stress reduction on psychological symptoms, quality of life, and marital satisfaction in infertile women undergoing IVF: A randomized clinical trial - Sayed Abolfazl Tavousi; Zahra Zanjani; Narmin Mohammadi; Abdollah Omidi (Kashan University of Medical Sciences, 2024)
Background: Infertility encompasses complex medical, psychological, social, and cultural challenges, significantly impacting those affected. The process of In Vitro Fertilization (IVF) often adds considerable stress.Objectives: This study investigated the effects of Mindfulness-Based Stress Reduction (MBSR) on the psychological health, quality of life, and marital satisfaction in infertile women undergoing IVF.Methods: This randomized controlled trial employed a consecutive sampling to include 44 women with infertility, undergoing IVF from September 2021 to February 2023. Participants were allocated into intervention and control groups, 22 each, through block randomization. The intervention group participated in an 8-week MBSR program, while the control group received education on parenting styles across four sessions. Assessment tools comprised the Brief Symptom Inventory, the brief World Health Quality of Life Questionnaire, and the Enrich Marital Satisfaction Questionnaire Short Form. Assessments were conducted at baseline, after the intervention, and two months after the intervention. Data analysis utilized the chi-square, t-test, and repeated measures analysis of variance.Results: The mean baseline psychological symptoms, quality of life, and marital satisfaction scores did not significantly differ between the two groups. The mean baseline score for psychological symptoms in the MBSR group was 109.36±19.52, which decreased to 77.82±19.89 and 58.82±9.26 immediately after and two months after the intervention (P<0.001). The mean baseline quality of life score in the MBRS group was 47.39±3.43 which increased to 54.70±3.90 and 59.71±3.57 in consecutive measurements (P<0.001). The mean score for marital satisfaction in the MBRS group was 123.59±19.44 and increased to 143.45±18.41 and 158±12.44 over time (P<0.001). In the control group, the mean psychological symptoms increased over time, but the quality of life and marital satisfaction did not change significantly.Conclusion: MBSR could significantly reduce psychological distress and enhance both the quality of life and marital satisfaction in infertile women undergoing IVF.